(untitled) (Revista Educação, Artes e Inclusão, 2024)
The objective of the research is to understand how graffiti art contributes as a device for the construction of the identity of young people in the Manguinhos favela complex, in the state of Rio de Janeiro. The region where the research was carried out, based on a case study, is part of (1) a territory that brings together fifteen favelas. We studied the “Brabas Crew” project, which has been operating in this space since 2017, promoting the reconfiguration of the environment, of spaces abandoned by civil society and the State. The project’s perspective is anchored in the consolidation of the rights of the participating subjects through the art of graffiti. The analytical theoretical centrality is in the studies of Costa (2005; 2007), Paula and Fravetto (2020) and others. The qualitative method was used, based on a case study, where unstructured interviews took place with the idealizing agents. We conclude that projects like this have the potential to motivate young people involved in the search for the expression of their rights and, consequently, in the construction of their identity as a subject when they expose, through graffiti, who they are and the needs they face in their daily lives and the from the favela.